Description of Hypertension Cases in The Krapyak Kidul Health Center Working Area in 2023 - Irawan, Teguh; Indriyani, Yulis; Rahmatika, Shilnia; Pratiwi, Farah Angelina; Anisa , Fadhilla; Falujatunnisa, Nirmala; Setiawan, Bagas Budi (MSJ : Majority Science Journal, 2024)
Hypertension is a major health problem that is significant globally, including in the working area of Krapyak Kidul Community Health Center, Pekalongan City. This study aims to provide an overview of hypertension cases in Krapyak Kidul Health Center in 2023. This type of research is descriptive using secondary data from hypertension reports available at Krapyak Kidul Health Center. The study was conducted from February 2024 to May 2024, with a total sample of 820 hypertension cases using total sampling technique. The study subjects included patients with an age range of 0-28 days to more than 65 years, with a focus on the productive age group (45-64 years) and the elderly (>65 years). The variables analyzed included age, gender, and type of hypertension case. Data were analyzed using SPSS (Statistical Package for the Social Sciences) with descriptive analysis method to identify the prevalence, demographic characteristics, and distribution of hypertension cases. The results of the study are expected to provide in-depth insight into the prevalence of hypertension and case characteristics in Krapyak Kidul Community Health Center. The findings will be useful for designing more effective health interventions, as well as supporting efforts to improve public health in the area.